EPCO-11. GATEKEEPER INACTIVATION DRIVES TUMOR PROGRESSION TO GRADE IV ASTROCYTOMA. (14th November 2022) - Hartewig, Anja; Granberg, Kirsi; Jaatinen, Serafiina; Tiihonen, Aliisa; Annala, Matti; Vuorinen, Elisa; Kivinen, Anni; Rauhala, Minna; Maass, Kendra; Pajtler, Kristian; Yli-Harja, Olli; Helén, Pauli; et al.
Abstract: IDH-mutant low-grade diffuse astrocytomas frequently progress to grade IV astrocytomas with implications for patient prognosis. To better understand this process, we applied whole-genome and transcriptome sequencing to matched tumor samples collected before and after progression to grade IV astrocytomas from five patients. All tumors carried an IDH1 mutation. The number of chromosomal rearrangements was increased between 1.3 and 3.5-fold in the tumors upon progression, with the exception of one case, in which the increase was only 1.03-fold. This case exhibited a hypermutation signature caused by homozygous deletion of the MSH2 gene, which encodes a member of the DNA mismatch repair complex. The most common genomic alterations acquired at progression were homozygous deletions in the CDKN2A/ RB1 -pathway or hemizygous deletion of PTEN . Additionally, PDGFRA was amplified in two grade IV tumors, with concordantly increased expression. For one of these cases, a PDGFRA -amplified subclone is likely to be present already in the low-grade astrocytoma. We further detected intrachromosomal rearrangements closeby the genes NRG3 in the progressed tumors as well as in the The Cancer Genome Atlas (TCGA) cohort. The expression of NRG3 decreased with increasing grade in the TCGA cohort and the gene was frequently deleted. Lower NRG3 expression was associated with shorter survival in the TCGA cohort. Several miRNAs showed differential expression upon progression. For two miRNAs the predicted targets were associated with cell cycle regulation and we detected inverse correlation between miRNA and target mRNA expression. While progression seems to occur via different pathways, the predicted outcome for many of the alterations was the inactivation of tumor suppressor genes and further dysregulation of cell proliferation.